Analysis of fatal-serious accidents and dangerous vehicle movements at access points on Malaysian Rural Roads - Mustakim, Fajaruddin (2014)
raffic accidents have been recognized as one of the major causes of human and economic losses in both developed and developing countries. In 20 l 0, Malaysia recorded a total of 414,421 accidents, resulting in an average of 19 deaths from road accidents every single day. This research analyzed the factors relevant to fatal and serious accidents on rural federal roads in Malaysia. The objective was to identify the dangerous vehicle movements and factors posing significant risks for fatal-serious accidents at access points (non-signalized minor junctions) and to suggest countermeasures. This research consists of seven Chapters. Firstly, Chapter l provides a discussion of accident trends and traffic studies in general. In Chapter 2, the scope was then narrowed down to focus on the accident black spot in order to identify the hazardous or black spot sections. Chapter 3 further examines the quantitative accident records and traffic characteristics for each of the selected sections. Next, Chapter 4 focuses on vehicle movements at non-signalized intersections. Chapter 5 provides the methodology and procedures adopted in the development of accident prediction models. Chapter 6 focuses on the development of gap acceptance model. Finally, Chapter 7 provides the development of serious conflict model. This research carries out numerous surveys to observe various traffic movements, including right and left turns, from minor and major roads, in addition to many other characteristics, in order to construct accident analysis models. One of the findings is that right-turn motorcycles caused serious conflicts and right tum movement was considered o be the most dangerous movement. Based on this finding, this research further examines the driver behavior of gap acceptance and serious conflicts using the proposed four gap patterns for a right-turn vehicle from minor to major roads at access points in Road Section 10 of the Federal Road 50 (Unchannelized intersection connected 2-lane minor and 4-lane major roads). In addition, further analysis is perfon:ned to identify the gap pattern and the factors relevant to serious conflicts. The results demonstrated thal right-turning vehicles, especially motorcycles, apparently intended to start turning right in a very short gap and the approaching speed and the gap between a pair of vehicles from opposite directions in the mainstream were the critical factors causing serious conflicts to the right-turn vehicles. In addition, this research studies more on the other two non-signalized intersections located in Road Sections 2 (Channelized intersection connected 2-lane minor and 6-lane major roads) and 9 (Unchannelized intersection connected 2-lane minor and 4-lane major roads with a traffic signal in close proximity) of the Federal Road 50. The results found that the existence of channelization on the intersection encouraged the right-tum vehicle to accept a longer gap. Furthermore, the combined analysis of all the three un-signalized intersections (Road Sections 2, 9 and 0), reveals that angular serious conflict, nose-tail conflict, and if the second vehicle in he pair in the mainstream is a motorcycle or a passenger car, can significantly influence the right-tum vehjcles to accept a short gap. On the other hand, a traffic light located in a relatively close distance to the access point, as well as channelization on the intersection can cause the right-tum vehicles to accept longer gaps.